Forceful or Funny? Audience Interpretations of Narrative Persuasion in Satirical Entertainment Media. Issue 4 (4th July 2021) - Tchernev, John M.; Brown, Christopher; Walther-Martin, Whitney; Moyer-Gusé, Emily
ABSTRACT: It has been established that narrative entertainment messages have the power to produce persuasive outcomes in audiences, but the specific message components that influence audience responses are not well understood. The current study uses focus groups to explore audience interpretations of meaning, perceptions of persuasive intent, and perceptions of the source of a persuasive message in response to a satirical narrative with an environmental theme. The results indicated that audiences define persuasive intent much more narrowly than researchers. Audiences also inferred meaning based on which characters espoused certain messages, but struggled to form conceptions of the creators behind the show or discern an overall persuasive intent. Furthermore, humor acted both as a factor in enjoyment of the narrative and as a discounting cue.